Defining standard enzymatic dissociation methods for individual brains and spinal cords in EAE - Hussain, Rehana Z. (Neurol Neuroimmunol Neuroinflamm, 2018)
OBJECTIVE: To determine the capacity, effectiveness, efficiency, and reliability of select tissue dissociation methods to isolate mononuclear cells from the CNS of mice with experimental autoimmune encephalomyelitis (EAE). METHODS: As part of an assay qualification, we tested the isolation method Percoll PLUS vs a commercially available enzymatic Neural Tissue Dissociation Kit (Kit), and the enzymes accutase and papain in C57BL/6 mice with active EAE. In a stepwise approach, we applied the following 4 criteria to each dissociation method: (1) mononuclear cell viability post-processing was required to be ≥80% per brain or spinal cord sample, (2) absolute live mononuclear cell numbers was required to be ≥5 × 10(5) per brain or spinal cord sample of mice with clinical EAE, (3) test-retest reliability had to be verified, and (4) the absolute mononuclear cell numbers in brain and spinal cord had to correlate with the EAE disease course. RESULTS: Enzymatic dissociations allowed for greatly increased cell yield and specifically allowed for downstream assays from individual brains and spinal cords in C57BL/6 mice with EAE. All enzymatic dissociations provided a more efficient and effective method for isolating mononuclear cells from brains and spinal cord. Only the Kit assay provided a significant correlation between absolute mononuclear cell numbers in the spinal cord and EAE disease severity. CONCLUSIONS: Enzymatic dissociation of CNS tissue of C57BL/6 mice with active EAE with the Kit should be the standard method. The identification of optimized CNS dissociation methods in EAE has the potential to identify cellular events that are pertinent to MS pathogenesis.